2002
DOI: 10.1126/science.1072891
|View full text |Cite
|
Sign up to set email alerts
|

A Natural Product That Lowers Cholesterol As an Antagonist Ligand for FXR

Abstract: Extracts of the resin of the guggul tree (Commiphora mukul) lower LDL (low-density lipoprotein) cholesterol levels in humans. The plant sterol guggulsterone [4,17(20)-pregnadiene-3,16-dione] is the active agent in this extract. We show that guggulsterone is a highly efficacious antagonist of the farnesoid X receptor (FXR), a nuclear hormone receptor that is activated by bile acids. Guggulsterone treatment decreases hepatic cholesterol in wild-type mice fed a high-cholesterol diet but is not effective in FXR-nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
367
2
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 478 publications
(381 citation statements)
references
References 35 publications
6
367
2
3
Order By: Relevance
“…Guggulsterone is an antagonist of the FXR, a key regulator of cholesterol homeostasis [33]. Recent studies demonstrate that FXR is expressed and functional in vascular endothelial cells indicating that FXR may play a role in endothelial homeostasis and serve as a novel molecular target for manipulating vascular inflammation [4,11,17].…”
Section: Discussionmentioning
confidence: 99%
“…Guggulsterone is an antagonist of the FXR, a key regulator of cholesterol homeostasis [33]. Recent studies demonstrate that FXR is expressed and functional in vascular endothelial cells indicating that FXR may play a role in endothelial homeostasis and serve as a novel molecular target for manipulating vascular inflammation [4,11,17].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that guggulsterone is an antagonist of farnesoid X receptor (12,13). In addition, guggulsterone has been shown to increase transcription of bile salt export pump (14).…”
Section: Introductionmentioning
confidence: 99%
“…For thousands of years, guggulsterone has been used to treat various human diseases, including inflammation, arthritis and cardiovascular disease (9)(10)(11). The active components of this herbal extract are the trans Z-and cis E-isomers of guggulsterone (12).…”
Section: Introductionmentioning
confidence: 99%